Exploring the Translation Lookaside Buffer (TLB) for Low-Level Task Differentiation and Classification - Cristian Agredo; Daniel F. Koranek; Christine M. Schubert Kabban; Jose A. Gutierrez Del Arroyo; Tor J. Langehaug; Scott R. Graham (IEEE Access)
The primary focus of modern Central Processing Unit (CPU) technologies is performance improvement, with security often considered a secondary concern. As a result, vulnerabilities within the system are overlooked. While significant research, both offensive and defensive, has been conducted on CPU caches, relatively little attention has been given to the Translation Lookaside Buffer (TLB) due to its perceived lack of data granularity. Prior studies have typically combined multiple Hardware Performance Counters (HPCs) or relied on timing analysis to extract meaningful insights. In contrast, this study introduces a novel methodology that leverages only TLB related hpc for multi-task classification, without incorporating data from other microarchitectural components such as caches or branch predictors, and without relying on timing memory accesses. In the proposed methodology, an attacker uses hpc to collect TLB based data while a victim executes tasks. We demonstrate that statistical learning models, including Random Forest (RF) and Logistic Regression (LR), achieve classification accuracy of up to 87%, surpassing the next best TLB only method (based on timing analysis) by 11%. Furthermore, neural networks, such as Artificial Neural Network (ANN) and Convolution Neural Network (CNN), achieve 88% accuracy, improving prior TLB based approaches by 12%. These findings demonstrate the potential of TLB based methodologies for task classification, victim monitoring, and future security enhancements in microarchitectural design.